2020
DOI: 10.1002/acn3.51182
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of polyneuropathy in Parkinson’s disease

Abstract: Objective: Previous studies in Parkinson's disease (PD) patients have demonstrated a high prevalence of polyneuropathy (PNP) and pronounced alpha-Synuclein pathology in dermal nerve fibers already at early disease stages. The aim of this study was to analyze associations between the prevalence and severity of PNP with nonmotor and motor symptoms in PD patients. Methods: Fifty PD patients were characterized comprehensively for the presence of clinical symptoms (nonmotor and motor), electrophysiologic alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
3
7
1
Order By: Relevance
“…In the present study, high levels of subjective neuropathic complaints in 87.5% of the MSA and 66.7% of the PSP patients were recorded by the patient self-report instrument NSS. Electrophysiological confirmation of PNP could be established in 50% of the MSA and 50% of the PSP patients, which considerably exceeds the rate of 7-9% in the normal elderly population [32,33], but is consistent with the reported PNP prevalence rates in PD, ranging from 16.3% up to 62% [9,34].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In the present study, high levels of subjective neuropathic complaints in 87.5% of the MSA and 66.7% of the PSP patients were recorded by the patient self-report instrument NSS. Electrophysiological confirmation of PNP could be established in 50% of the MSA and 50% of the PSP patients, which considerably exceeds the rate of 7-9% in the normal elderly population [32,33], but is consistent with the reported PNP prevalence rates in PD, ranging from 16.3% up to 62% [9,34].…”
Section: Discussionsupporting
confidence: 86%
“…While NSS in PD patients significantly correlated with motor, non-motor symptoms as well as poor quality of life in our study, we found a significant correlation between NSS and UPDRS part III in PSP patients, including within the subscales of midline function and lower limb bradykinesia. Regarding electrophysiological alterations, Kühn et al reported a correlation between motor nerve amplitudes in PD patients and motor impairment, disease duration and age [9]. Lower tibial cMAP amplitude in MSA patients in our study was associated with higher UMSARS II scores as well as UPDRS III scores, including midline function (facial expression, posture, gait) and lower limb bradykinesia.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations